Effects of Moringa Leaf Extract and Moderate Intensity Exercise on Histopathological Appearance and Autophagy Gene Expression - Gunadi, Julia Windi; Jatnika, Danti Dja; Astrid, Stephanie; Lucretia, Teresa; Ray, Hamidie Ronald Daniel; Goenawan, Hanna; Tarawan, Vita Murniati; Nurhayati, Titing; Lesmana, Ronny (Universitas Pendidikan Indonesia, 2021)
The prevention of liver disease could be conducted through preventive strategies, such as antioxidants and exercise. Moringa leaf extract has substances that could act as antioxidant, while exercise is also known protecting the liver from disease by changing hepatic metabolism and autophagy. This study aimed to investigate the effect of moringa leaf extract and moderate intensity exercise on histopathological appearance and autophagy gene expression of wistar rat liver. The method used in this study was animal experiment using 24 male wistar rats divided into 4 groups, including control group, moringa group, exercise group, and moringa + exercise group. Moringa leaf extract was given in low dose (5.7 mg/kgW) per oral, 5 times a week, for 4 weeks. Meanwhile, the 20 m/minute treadmill exercise was given for 30 minutes per day, 5 times a week, for 4 weeks. Results showed a significant change on histopathological scoring in exercise group (p=0.011) compared to control group. Increased autophagy gene expression was found in moringa + exercise group compared to control group (LC3 0.90 fold; p62 0.87 fold). In summary, this study presented that moderate intensity exercise induced changes on histopathological appearance of wistar rat liver that might be associated with physiological inflammation. Moringa, with its antioxidant properties, combined with increased autophagy might improve histopathological changes in moringa + exercise group.